Technological capability, relational capability and firms’ performance: The role of learning capability - Yakubu Salisu; Lily Julienti Abu Bakar (REGE Revista de Gestão, 2020)
Purpose – The purpose of this paper is to empirically evaluate the mediating role of learning capability on the relationship between technological capability, relational capability and small and medium enterprises (SMEs) performance in developing economy of Africa. Design/methodology/approach – A quantitative survey design was employed to collect the data from owner/manager of manufacturing SMEs in Nigeria. Partial least square structural equation model was used in the evaluation of both the measurement and structural models to determine the reliability and validity of the measurement and test the hypotheses, respectively. Findings – The statistical result indicates a positive relationship between technological capability, learning capability and SMEs performance. Equally, relational capability significantly and positively relates to SMEs learning capability. However, relational capability negatively relates to SMEs performance, while technological capability also negatively relates to learning capability. Furthermore, learning capability mediates the negative relationship of relational capability and SMEs performance to significant positive relationship, while it does not mediate the relationship of technological capability and performance. Research limitations/implications – The analysis of this study is restricted to only resource-based view and dynamic capability theory. Data of the study were collected once a time on a self-reported technique. The study contributed significantly to the body literature on technological and relational capabilities and performance. It also demonstrated the need for SMEs manager to recognize and appreciate the roles of these strategic capabilities in achieving sustainable competitive position. Practical implications – Through relational capability SMEs develops efficient collaborative relationship to acquire new techniques, knowledge. This is specifically, essential for SMEs firms from less developing and emerging economies as they are lagging behind at the global competitive platform, and that the possession of specific advantage locally may not be adequately enough to help penetrate the global markets. Similarly, technological capability enable firms to identify acquire and apply new external knowledge to develop operational competencies which may lead to the attainment of superior performance. Social implications – Government policies and programs designed to support technological development and innovation must be adjusted to consider the peculiar nature of SMEs firms in terms of technology and innovativeness that enhances competitive position and performance. Originality/value – This study empirically examined the relationship of technological and relational capabilities and the SMEs learning capability and performance.